2012
DOI: 10.1371/journal.pone.0045971
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to Malaria in Plasmodium vivax Infection: A Study in Central China

Abstract: Background P. vivax infection is characterised by relapsing fever, indicating reinfection by previously hidden parasites in the host. Relapsed infection can lead to the activation of the memory T cell pool, which may lead to protective immunity. This study aims to characterise immune responses in acute P. vivax-infected patients living in an area of central China characterised by only P. vivax infection.Methodology/Principal FindingsWe conducted a cross-sectional immune-phenotypic analysis of adults using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Nevertheless, cell-mediated response seems unaffected as evidenced in studies during the convalescent period in P. vivax-infected hosts, thus confirming a T cell-specific response, which was also reactive to P. falciparum antigens [104,107].…”
Section: Specific Antimalarial Immunity During Pregnancysupporting
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, cell-mediated response seems unaffected as evidenced in studies during the convalescent period in P. vivax-infected hosts, thus confirming a T cell-specific response, which was also reactive to P. falciparum antigens [104,107].…”
Section: Specific Antimalarial Immunity During Pregnancysupporting
confidence: 53%
“…In regions where different species of malaria parasites are endemic, it has been observed that immune response to P. falciparum interferes with the immune factors observed in P. vivax malaria [104] as confirmed by the strain-specific and serological crossreactive immunity between blood stage antigens of both species [5,105,106]. Nevertheless, cell-mediated response seems unaffected as evidenced in studies during the convalescent period in P. vivax-infected hosts, thus confirming a T cell-specific response, which was also reactive to P. falciparum antigens [104,107].…”
Section: Specific Antimalarial Immunity During Pregnancymentioning
confidence: 99%
“…The co-culture experiments were carried out with slight modification as described [41], [66]. In detailed, 100 µl/well was set up as a volume system in 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was examined by trypan blue exclusion staining. Co-culture experiments were carried out as described previously [30,33,34]. Culture volumes of 100 µL per well in a 96-well plate were used, with the ratio of antigen cells to PBMCs kept at 1 : 100.…”
Section: Isolation Of Pbmcs and T Cells And Proliferation Assaymentioning
confidence: 99%